Cloning of the structural gene (ompA) for an integral outer membrane protein of Escherichia coli K-12. - Henning, U (1979)
The gene (ompA) for the major outer membrane protein II* from Escherichia coli K-12 has been cloned on a 5-megadalton EcoRI fragment by using phage lambda as vector. The gene is expressed during the lytic cycle of the recombinant phage and the insoluble membrane-bound protein was detected in phage plaques with a simple radioimmunoassay. Transfer of the EcoRI fragment into plasmid pSC101 and expression in a host lacking protein II* led to overproduction of protein II* and decreased production of two other major outer membrane proteins. Expression of the plasmid pSC101-ompA+ in minicells derived from an ompA minicell-producing strain led to synthesis, at high rates, of this protein and massive accumulation of a second cell envelope protein most likely representing the biosynthetic precursor of protein II*.